ESGE Survey: worldwide practice patterns amongst gastroenterologists regarding the endoscopic management of Barrett’s esophagus - Dunn, Simon J.; Neilson, Laura J.; Hassan, Cesare; Sharma, Prateek; Guy, Claire; Rees, Colin J. (Endoscopy International Open, 2016)
Background and study aims: Barrett’s esophagus is a common condition that is widely encountered in clinical practice. This European Society of Gastrointestinal Endoscopy (ESGE) survey aimed to determine practice patterns amongst European clinicians with regard to the diagnosis and management of Barrett’s esophagus.Methods: Clinicians attending the ESGE learning area at the United European Gastroenterology Week in 2014 were invited to complete a 10-question survey. This survey was programed on to two Apple iPads. Information was gathered with regard to demographics, practice settings, and diagnosis and management strategies for Barrett’s esophagus. Results: In total, 163 responses were obtained. Over half of respondents (61 %) were based in university hospitals, the majority (78 %) were aged 30 – 50 and half had more than 10 years’ experience; 66 % had attended courses on Barrett’s esophagus and more than half (60 %) used the Prague C & M classification. Advanced imaging was used by 73 % of clinicians and 72 % of respondents stated that their group practiced ablation therapy. Most (76 %) practiced surveillance for non-dysplastic Barrett’s, 6 % offered ablation therapy in some situations, and 18 % offered no intervention. For low grade dysplasia, 56 % practiced surveillance, 19 % ablated some cases and 15 % ablated all cases. In total, 32 % of clinicians referred high grade dysplasia to expert centers, with 20 % referring directly for surgery and 46 % using ablation therapy in certain cases. Endoscopic mucosal resection was the most commonly used ablation technique (44 %). Conclusions: There has been reasonable uptake of the Prague C & M classification for describing Barrett’s esophagus, and ablation is widely practiced. However, practice patterns for Barrett’s esophagus vary widely between clinicians with clear guidance and quality standards required.